Ulysses Explained How Homer, Dante, and Shakespeare Inform Joyce’s Modernist Vision - Weir, David. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
When it comes to James Joyce's landmark work, Ulysses , the influence of three literary giants, Homer, Shakespeare, and Dante, cannot be overlooked. Examining Joyce in terms of Homeric narrative, Dantesque structure, and Shakespearean plot, Weir rediscovers Joyce's novel through the lens of his renowned predecessors.